Food security challenges during and post movement restrictions of COVID-19 in Southeast Asia - Yasmin Beng Houi Ooi; Ramzah Dambul (2020)
Following the global health crisis brought about by the SARS-CoV-2 coronavirus which causes COVID-19, food security has become or will become an issue in most countries.  Most countries have some form of movement restrictions in place as a public health measure to ‘flatten the curve’, i.e., to slow down the community spread and thus avoiding as much as possible overwhelming the capacity of health services to treat patients. In most countries, movement restrictions excluded transportation and movement of food and agricultural produce.  However in reality, the supply chain of food from farm to table was disrupted. Most consumers in Southeast Asia rely on retail supply chains other than supermarkets and hypermarkets. These include grocery shops, road side stalls and pop-up weekly markets which are usually supplied by smallholder farmers. During movement restriction orders, low income consumers and smallholder farmers experienced food insecurity.  For the latter, they had piles of unsellable vegetables and fruits which compromised their ability to replant the next batch of crops; thus plunging them into economic hardship.  Policy makers should consider a new supply chain model that connects farmers directly to consumers as movement restriction orders have shown that the old model of farmers - middlemen - consumers was problematic. Post COVID-19 pandemic, food security planning must take into account climate change and livelihood of smallholder farmers, other than issues of availability, affordability, accessibility and utilisation.  Generally Southeast Asian countries have yet to achieve resilience to climate change.  Post pandemic, agriculture extension work that includes processing of harvests could be considered to increase the livelihood of smallholder farmers, as well as monetising farm work which had usually been unpaid.  Addressing food security for all should include the lowest denominator that are most vulnerable, which in many places are low income households including smallholder farmers, women and particularly low income women, and foreign manual workers.